2011
DOI: 10.1002/ccd.22767
|View full text |Cite
|
Sign up to set email alerts
|

Six‐month clinical follow‐up of the tryton side branch stent for the treatment of bifurcation lesions

Abstract: In a real world the use of the Tryton Sidebranch stent is associated with good procedural safety and angiographic success rate and acceptable outcome at six months of follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1
1

Year Published

2012
2012
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 41 publications
2
17
1
1
Order By: Relevance
“…The Tryton stent is one such dedicated bifurcation device, which is used in combination with a work-horse DES, and could therefore be considered a two-stent technique. Two clinical studies on this device have been previously published: a First-In-Man (FIM) study and a two-centre registry [5,24]. Compared with these two previously published clinical studies on the Tryton stent, the current study showed slightly better clinical outcomes concerning MI (FIM 6.6 %, twocentre registry 3 %), comparable outcomes on TLR (FIM 6.6 %, two-centre registry 4 %), and stent thrombosis (no stent thrombosis in either the FIM or the twocentre registry), and slightly worse outcomes on cardiac deaths (FIM 3.3 %, two-centre registry 1 %).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Tryton stent is one such dedicated bifurcation device, which is used in combination with a work-horse DES, and could therefore be considered a two-stent technique. Two clinical studies on this device have been previously published: a First-In-Man (FIM) study and a two-centre registry [5,24]. Compared with these two previously published clinical studies on the Tryton stent, the current study showed slightly better clinical outcomes concerning MI (FIM 6.6 %, twocentre registry 3 %), comparable outcomes on TLR (FIM 6.6 %, two-centre registry 4 %), and stent thrombosis (no stent thrombosis in either the FIM or the twocentre registry), and slightly worse outcomes on cardiac deaths (FIM 3.3 %, two-centre registry 1 %).…”
Section: Discussionmentioning
confidence: 99%
“…The Tryton stent could potentially optimise side branch ostium scaffolding, while minimising the amount of metal in the main branch [4]. A previous twocentre registry has shown promising procedural and clinical outcomes after placement of this dedicated device [5]. To confirm these observations, we investigated procedural success and clinical outcomes after treatment of BLs with the Tryton stent in 91 consecutive patients treated for BLs in our own centre.…”
Section: Introductionmentioning
confidence: 99%
“…Initial reports have been very promising, and published series have presented procedural success rates with this device of around 94% with periprocedural MI rates of 2 and 7% . Clinical follow‐up in these series was limited to 6 months with MACE rates of 10% in the initial experience , and 6% in a larger all‐comer registry .…”
Section: Discussionmentioning
confidence: 99%
“…The dedicated TRYTON Side‐Branch Stent™ (TRYTON Medical, Durham, NC) , used in conjunction with a conventional stent, intends to simplify a more technically demanding conventional culotte stenting procedure, by maintaining similar SB scaffolding while simultaneously improving branch access. Favorable acute clinical, angiographic and optical coherence tomography (OCT) results after TRYTON stenting have been reported, as well as 6‐month clinical and angiographic outcomes . We performed an in‐depth multimodality follow‐up analysis to understand better the complex interplay of device characteristics, stenting technique, healing processes, and hemodynamic and clinical outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Both these registries show that the treatment of bifurcation lesions with a dedicated Tryton stent is safe and feasible, with good technical and procedural success and low major adverse cardiac events at 6-month clinical follow-up [11].…”
Section: Resultsmentioning
confidence: 96%